2016
DOI: 10.1038/srep39499
|View full text |Cite
|
Sign up to set email alerts
|

Persistent p55TNFR expression impairs T cell responses during chronic tuberculosis and promotes reactivation

Abstract: The pleiotropic activities of TNF are mediated by two structurally related but functionally distinct type I transmembrane receptors, p55TNFR and p75TNFR expressed in most cell types, that can be cleaved and act as TNF scavengers. Here, we investigated the effect of persistent p55TNFR cell surface expression during aerosol inhalation challenge with virulent M. tuberculosis H37Rv. We demonstrated that persistency of p55TNFR in macrophage cultures increased the synthesis of soluble TNF, p75TNFR and NO, however, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 70 publications
(92 reference statements)
2
15
0
Order By: Relevance
“…To study the effect of TNFRp75 in regulating macrophage functions, our initial experimental approach incorporated a bone marrow‐derived macrophages (BMDM) culture system, which we and others have used extensively to study macrophage responses to M . tuberculosis 34,35 . We first confirmed constitutive expression of TNFRp75 in unstimulated WT BMDM (Figure 1A).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…To study the effect of TNFRp75 in regulating macrophage functions, our initial experimental approach incorporated a bone marrow‐derived macrophages (BMDM) culture system, which we and others have used extensively to study macrophage responses to M . tuberculosis 34,35 . We first confirmed constitutive expression of TNFRp75 in unstimulated WT BMDM (Figure 1A).…”
Section: Resultssupporting
confidence: 54%
“…Release of soluble TNFRp55 has been described to regulate macrophage activation and apoptosis during mycobacterial infection 34,36 . We have previously found that TNFRp75 deficiency is associated with the release of less TNFRp55 from DCs during M .…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Although a complex regulatory process, TNF-α is known to be an important factor that facilitates DC maturation towards specific T cell priming (59,60). Interestingly, while persistent TNFRp55 expression leads to potential defective T cell responses during chronic M. tuberculosis infection (61), sustained TNF-α expression by DCs enhances maturation and generates a much more robust T cell response (62). Thus, DCs are positioned to serve as an important link between innate and adaptive immunity and may act as useful targets for immunotherapy and vaccine development (63,64).…”
Section: Antigen Presentationmentioning
confidence: 99%